The Economic Impact of Climate Change on Rural Children's Educational Enrollment in Dambatta Kano State - Salisu, Abduljalal; Hindrayani, Aniek; Setyowiboyo, Feri (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This study explores the interrelationships between climate change, agricultural productivity, household income, and student enrollment in rural areas of Dambatta Local Government Area, Kano State. Utilizing a linear regression model, the research reveals a moderate but significant negative impact of climate change on agricultural productivity, indicating that climate change accounts for 53.5% of the variability in agricultural productivity. Additionally, a strong positive correlation (r = 0.642) and a sample size of 108. The p-value of 0.000, which is significantly less than 0.05, confirms the statistical significance of this correlation, indicating that increases in agricultural productivity are closely associated with increases in household income in the studied region. The findings were found between agricultural productivity and household income, suggesting that decreases in agricultural output directly reduce household income. Furthermore, the study shows that household income significantly predicts student enrollment in schools, revealing that nearly 60% of the variability in student enrollment can be explained by changes in household income. These findings underscore the broader socio-economic implications of climate change in rural areas, emphasizing the need for targeted policies to mitigate climate impacts, support rural livelihoods, and ensure educational access. The study contributes to a deeper understanding of the cascading effects of climate change on rural communities, providing a foundation for future research and policy interventions